Time-Varying Effect of Ductile Flexural Toppling Failure on Antidip Layered Rock Slope - Cai, Junchao; Zheng, Da; Ju, Nengpan; Wang, Jue; Zhou, Xin; Li, Da (Frontiers in Earth Science, 2022)
Ductile flexural toppling failure is a common form of toppling failure, which is the product of long-term geological history and has the characteristics of secular distortion and progressive failure. Based on the thought of deformation stability analysis, we divided flexural toppling failure into four stages: start-up stage, rapid deformation development stage, transient stability stage and long-term creep development stage. Combined with mechanical analysis, the developmental conditions of the start-up stage, the transient stability stage and the long-term creep development stage are discussed respectively. Finally, several cases were selected to analyze the stage and the stability of the toppling deformation body, and verify the rationality of the mechanical analysis condition. Research results show that the start-up conditions meet the equation (2), the rock layer inclination and slope angle is 0.5π-φ in transient stability stage, that angle is the infinite 0.5π in long-term creep stage. Other external forces (such as water pressure) will intensify the development of ductile flexural toppling failure, so that the angle between the toppled bedding surface and the slope surface increases. There is of great significance to analyze the development stage of the ductile flexural toppling, using the concept of deformation stability to comprehensively analyze and evaluate the stability of the ductile flexural toppling, reasonably develop and utilize its self-stability ability, and set up support measures.